Critical Review Selecting a Proper Law to Resolve Sexual Violence Against Children - Aprilianda, Nurini; Farikhah, Mufatikhatul; Krisna, Liza Agnesta (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2022)
This article was written based on the results of research aimed at finding the right choice in resolving cases of sexual violence against children in Aceh, namely between the Child Protection Law or the Qanun Jinayat. This research is empirical legal research with a case study approach. The data collection technique used were interviews with key informants and document studies, namely court decisions. This study found differences in the application of different laws to the same case. Even though children as victims of sexual violence not only have an impact on physical trauma, they also experience psychological trauma which can cause mental disorders. Data for the last 3 (three) years shows that until now law enforcers have not been consistent in applying the law to the settlement of these cases. Our finding is that there are differences of opinion between law enforcers because the two arrangements are specific criminal law in nature. Therefore, the principle of systematic lex specialist is very important as a basis for law enforcement in determining the right choice of law for the settlement of these cases.